Management Controls that Anchor other Organizational Practices - Ahrens, Thomas (Contemporary Accounting Research, 2018)
Abstract How do management control practices structure other organizational practices? This paper proposes a theory of practice hierarchies. The key idea is that organizations possess constitutive rules that define their character. They are enacted by the practices at the top of the hierarchy. These “anchor practices” contain objectives and established ways of doing things that control, or structure, subsidiary practices. They do so by defining key social relationships in the organization, often ones that are antagonistic. The paper uses illustrations from a longitudinal field study of a retail bank and draws on insights from cultural sociology.